Assistive Technology Tools for Learning Physics Courses for Students with Special Needs - Dian Nugraha; Mohamad Zaenudin; Safira Faizah (Jurnal Informatika Universitas Pamulang, 2023)
The spread of digital information has grown very rapidly and has become a common tool used by all people. This is in line with the development of various infrastructures and digital ecosystems for all lines of life in all fields without exception, especially in this paper which discusses the development of information technology in the field of education. Because in essence education can play an active role in developing the potential of students to develop religious spiritual values, self-discipline, personality, intelligence, noble personality, and abilities that are beneficial to themselves, society, the state, and the Indonesian nation. In line with the vision and mission of Jakarta Global University which concentrates learning on student centered which refers to 21st century learning, where learning is focused on the use of information technology to trigger a learning process that focuses on student learning experience. The development of this system aims to make it easier for students with special needs to understand physics concepts by using simulation methods assisted by modules and other learning tools that can be used by students with special needs, especially for students with hearing disorders. SUS Questionnaire are distributed to get after the posttest to get usability test for the system. Tests using Cronbach's Alpha have been used to find the value of validity and reliability by obtaining an average result of 0.702 for reliability and 0.312 for validity testing. This shows that the developed system can be used easily thanks to the optimization of the features that the author has implemented in the CDIES system to facilitate the needs of students with disabilities.